Experiences of first year undergraduate nursing students using Instagram in their clinical practicum during COVID-19 pandemic: A qualitative study. (December 2022) - Cachón-Pérez, José Miguel; González-Sanz, Pilar; Carretero-Ríos, María Ángeles; Soriano-Martin, Pedro; Rodríguez-García, Marta; García-García, Esther; Palacios-Ceña, Domingo
Abstract: Background: Social media provides us with easy access to information. For students, it is an additional learning resource used in different types of theoretical and practical teaching methodologies. Objectives: The aim of this paper was to describe the perspective of undergraduate nursing students on the use of Instagram during their clinical practicums in the midst of the COVID-19 pandemic. Design: A qualitative descriptive and exploratory study based on an interpretative framework. Settings and Participants: First-year undergraduate nursing students at the Universidad Europea de Madrid were included. Methods: In-depth interviews and researchers' field notes were used to collect the data. Purposive sampling and inductive thematic analysis were applied. During the interviews, themes such as accompaniment during practicums or training opportunities were identified. Results: The use of Instagram helped students to feel closer to professors, identifying it as an opportunity to remedy the possible lack of connection between theory and practice. Moreover, Instagram helped them build an image of nursing in clinical practicum environments. By using Instagram, undergraduate nursing students were able to better integrate and apply the knowledge acquired at university during their clinical practicums in hospitals. Conclusions: Our results can be applied to future studies on the use of social media platforms as teaching tools in clinical practicum settings and to observe the evolution of the image and role of nursing and its relationship with social media.